Efficacy of nalfurafine hydrochloride in patients with chronic liver disease with refractory pruritus: A randomized, double‐blind trial. Issue 10 (24th November 2016) - Kumada, Hiromitsu; Miyakawa, Hiroshi; Muramatsu, Taro; Ando, Naoki; Oh, Takanori; Takamori, Kenji; Nakamoto, Hidetomo
Abstract : Aims: Patients with chronic liver disease sometimes develop cholestasis, which induces severe whole‐body pruritus that may disrupt daily activities and sleep. To determine the efficacy of nalfurafine hydrochloride (5 μg), which is a selective κ‐opioid receptor agonist, in improving pruritus, we undertook a double‐blind placebo‐controlled study in patients with chronic liver disease with refractory pruritus. Nalfurafine hydrochloride at 2.5 μg was also used to evaluate the dose–response relationship. Methods: In total, 318 subjects were randomly assigned to receive the placebo or nalfurafine hydrochloride (2.5 or 5 μg) given orally once daily for 84 consecutive days. Pruritus was assessed based on the visual analog scale and pruritus scores. Results: Changes in the visual analog scale at week 4 (last observation carried forward) were significantly greater in the nalfurafine hydrochloride groups at 28.56 and 27.46 mm in the 2.5 μg and 5 μg groups, respectively, compared to 19.25 mm in the placebo group ( P  = 0.0022 and 0.0056, respectively). The major adverse drug reactions (ADRs) included pollakiuria (including nocturia), somnolence, insomnia (including middle insomnia), and constipation. Most ADRs were mild. Conclusions: Nalfurafine hydrochloride (2.5 or 5 μg daily) was effective in the treatment of refractory pruritus in patients with chronic liver disease. Furthermore, no clinically significant ADRs were observed at either dose.